Distribution and Ecology of Cytotypes of the Aster amellus Aggregates in the Czech Republic - MANDÁKOVÁ, TEREZIE (Oxford University Press, 2006)
• Background and Aims Polyploidy is viewed as an important mechanism of sympatric speciation, but only a few studies have documented patterns of distribution and ecology of different cytotypes in their contact zone. Aster amellus agg. (Asteraceae) is one of the species with documented multiple ploidy levels. The aim of this study was to determine spatial distribution and ecology of two cytotypes, diploid (2n = 18) and hexaploid (2n = 54), of Aster amellus agg. at their contact zone in the Czech Republic. • Methods Root-tip squashes and flow cytometry were used to determine the ploidy of 2175 individuals from 87 populations. To test whether some differences in ecology between the two ploidy levels exist, in each locality relevés were recorded and abiotic conditions of the sites were studied by estimating potential direct solar radiation, Ellenberg indicator values and above-ground biomass. • Key Results Together with diploid and hexaploids, minorite cytotypes (triploid, pentaploid and nonaploid) were found. No significant ecological differences between diploid and hexaploid cytotypes were found. In spite of this, no population consisting of both of the two basic cytotypes was found. • Conclusions The results of this study show that the contact zone of diploid and hexaploid cytotypes in the Czech Republic is much more diffuse than indicated in previous records. Although populations of both cytotypes occur in close proximity (the closest populations of different cytotypes were 500 m apart), each individual population consists of only one basic ploidy level. This was unexpected since there are no clear differences in abiotic conditions between populations. Taken together with the absence of an intermediate tetraploid cytotype and with reference to published world distributional patterns of different ploidy levels, this suggests a secondary contact zone. Detailed genetic study is, however, necessary to confirm this.